Respuesta :
Answer:
x = -1
Step-by-step explanation:
3x - 10x + 5 = 5x + 17 (collect like terms)
-7x + 5 = 5x + 17 (subtract 5x on both sides)
-12x + 5 = 17 ( subtract 5 on each side)
-12x = 12 ( divide by -12 on each side)
x = -1
Answer:
x = - 1
Step-by-step explanation:
[tex]3x - 10x + 5 = 5x + 17[/tex]
Add the like terms.
[tex] - 7x + 5 = 5x + 17[/tex]
Add 7x to both sides.
[tex]5 = 12x + 17[/tex]
Subtract 17 from both sides.
[tex] - 12 = 12x[/tex]
[tex] - \frac{12}{12} = x[/tex]
[tex] - 1 = x[/tex]